2018
DOI: 10.1038/s41598-018-20856-6
|View full text |Cite
|
Sign up to set email alerts
|

A cleavage product of Polycystin-1 is a mitochondrial matrix protein that affects mitochondria morphology and function when heterologously expressed

Abstract: Recent studies have reported intrinsic metabolic reprogramming in Pkd1 knock-out cells, implicating dysregulated cellular metabolism in the pathogenesis of polycystic kidney disease. However, the exact nature of the metabolic changes and their underlying cause remains controversial. We show herein that Pkd1ko/ko renal epithelial cells have impaired fatty acid utilization, abnormal mitochondrial morphology and function, and that mitochondria in kidneys of ADPKD patients have morphological alterations. We furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 78 publications
11
86
2
3
Order By: Relevance
“…Mitochondrial mass, on the contrary, is preserved in the proximal tubules of Ksp‐Cre;Pkd1 flox/− kidneys (KO, cortex) as expected (Figure 1C and S1B). In the cystic epithelia, we observed swollen mitochondria as previously reported either in situ 10 or on isolated cells derived from Pkd1 mutant mice, 11 with few cristae and decreased electron density within the matrix, both in the cortex and in the medulla. Of interest, we also detected healthy, and normally appearing mitochondria scattered among damaged ones in the cysts suggesting that the absence of PC‐1 does not per se result in this structural damage.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Mitochondrial mass, on the contrary, is preserved in the proximal tubules of Ksp‐Cre;Pkd1 flox/− kidneys (KO, cortex) as expected (Figure 1C and S1B). In the cystic epithelia, we observed swollen mitochondria as previously reported either in situ 10 or on isolated cells derived from Pkd1 mutant mice, 11 with few cristae and decreased electron density within the matrix, both in the cortex and in the medulla. Of interest, we also detected healthy, and normally appearing mitochondria scattered among damaged ones in the cysts suggesting that the absence of PC‐1 does not per se result in this structural damage.…”
Section: Resultssupporting
confidence: 84%
“…In this study, we show that in cystic kidneys due to Pkd1 inactivation, epithelial cells of the distal tubules and collecting ducts have reduced mitochondrial mass and decreased activity of mitochondria RCCs in vivo. Mitochondria also appear swollen and damaged as previously reported in human tissues 10,11 . Of interest, we also found healthy mitochondria scattered among aberrant ones, suggesting that the lack of Pkd1 is not per se sufficient to cause mitochondrial damage and that perhaps a progressive degeneration of mitochondria occurs in these tissues.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This in turn enhances proliferation via extracellular signal‐related kinase 1 and 2 activation . In addition, a recent study suggested a direct role of polycystin‐1 in regulating mitochondrial function in renal epithelial cells . These various findings indicate that mitochondria and O 2 ˙− play important roles in the pathogenesis of ADPKD.…”
Section: Ros and Rns In Chronic Kidney Diseasementioning
confidence: 95%